New fuel governed combustion synthesis and improved luminescence in nanocrystalline Cr3+ doped ZnAl2O4 particles - N. Srinatha; S. Satyanarayana Reddy; N. Suriyamurthy; K.J. Rudresh Kumar; M.R. Suresh Kumar; A. Madhu; Basavaraj Angadi (Results in Optics, 2022)
This paper describes the solution combustion (SCS) synthesis of nanocrystalline Cr3+ doped ZnAl2O4 (ZAC) particles using a new efficient fuel. A thorough investigation was conducted to comprehend the interaction of dopant (Cr3+) and ZnAl2O4 host matrix, as well as the influence of doping on their structural, optical, and luminescence characteristic properties. The powder samples were thoroughly characterized using XRD, UV–Visible Diffuse Reflectance, and Photoluminescence spectroscopic techniques. The XRD analysis demonstrates the formation of polycrystalline nanoparticles, as well as a decrease in crystallite size with increasing Cr3+ concentration. The band gap energy red-shifted as Cr3+ was incorporated into the host matrix. The diffuse reflectance spectra show two absorption peaks at 395 nm and 540 nm are assigned to the 4A2g →4T1g and 4A2g →4T2g characteristic transitions of Cr3+ ions. The PL emission spectrum, on the other hand, shows four distinct peaks, indicating the manifestation of Cr3+ ions in octahedral symmetry, that is, Cr3+ ions in a strong crystal field. Increases in Cr3+ concentration result in luminescence enhancement up to x = 0.07 and suppression of luminescence observed beyond that concentration. In addition, the dopant ion's Racah parameters, crystal field parameters, and local site symmetry are calculated.